Boom-Bust Turnovers of Megabase-Sized Centromeric DNA in Solanum Species: Rapid Evolution of DNA Sequences Associated with Centromeres - Zhang, Haiqin; Koblížková, Andrea; Wang, Kai; Gong, Zhiyun; Oliveira, Ludmila; Torres, Giovana A; Wu, Yufeng; Zhang, Wenli; Novák, Petr; Buell, C Robin; Macas, Jiří; Jiang, Jiming (The Plant cell, 2014)
Centromeres are composed of long arrays of satellite repeats in most multicellular eukaryotes investigated to date. The satellite repeat-based centromeres are believed to have evolved from "neocentromeres" that originally contained only single- or low-copy sequences. However, the emergence and evolution of the satellite repeats in centromeres has been elusive. Potato (Solanum tuberosum) provides a model system for studying centromere evolution because each of its 12 centromeres contains distinct DNA sequences, allowing comparative analysis of homoeologous centromeres from related species. We conducted genome-wide analysis of the centromeric sequences in Solanum verrucosum, a wild species closely related to potato. Unambiguous homoeologous centromeric sequences were detected in only a single centromere (Cen9) between the two species. Four centromeres (Cen2, Cen4, Cen7, and Cen10) in S. verrucosum contained distinct satellite repeats that were amplified from retrotransposon-related sequences. Strikingly, the same four centromeres in potato contain either different satellite repeats (Cen2 and Cen7) or exclusively single- and low-copy sequences (Cen4 and Cen10). Our sequence comparison of five homoeologous centromeres in two Solanum species reveals rapid divergence of centromeric sequences among closely related species. We propose that centromeric satellite repeats undergo boom-bust cycles before a favorable repeat is fixed in the population.